Trade-Offs Between Investors' Perceptions of Risk, Returns, Service Quality, and Mutual Fund Investments - Kaushik, Sanjay; Kamboj, Garima; Kakkar, Diksha (Indian Journal of Finance, 2013)
On the one hand, investors perceive mutual funds to be riskier and a less rewarding investment channel as compared to the risk-free investments, and this leaves them dissatisfied. On the other hand, the volatile market has turned most of the investors to hold stocks with calculated risk, in the shape of mutual funds, to save themselves from the volatile market. Keeping this scenario in mind, understanding the investors' perception of mutual funds has become imperative as mutual funds can now prove to be the most preferred financial avenue, provided they are put forth before investors in the desired form. Investors' purchase decision for mutual funds is influenced by a chain of factors. Out of the list of factors, the perception of risk and satisfaction from returns have been found to be dominant. Other factors accountable for their final decision are quality of service delivered, cost of transaction, name familiarity, and so forth. The present paper aimed to identify the perceived relationship between investors' (respondents) risk, returns, service quality, and investment decisions. Furthermore, it investigated the impact of three factors - the perceived quality of services, name familiarity, and price - on respondents' mutual fund selection decision. It also studied the impact of the respondents' age, income, education, risk and returns perceptions on the choice between various financial avenues. Data were collected from 250 respondents using a structured questionnaire with pre-explained objectives of research. Reliabilities were tested using Cronbach's alpha. Furthermore, ranking and rating methodology was also used to prioritize the respondents' preferences. Chi square statistic was used to establish the factors that were significantly affected by the selected dimensions. Also, step-wise regression analysis was performed to identify the predictors of the intention to invest in mutual funds. Facts revealed in this study highlight the preferences of varied investors who desire to invest in mutual funds. The critical gaps identified in the study provide key information inputs regarding the discrepancies in the risk, returns, and service quality perceptions of the respondents, which can be extremely beneficial to AMCs in designing more lucrative solutions to suit their expectations.